Study of pedestrians’ mixed thermal responses when experiencing rapid and simultaneous variations in sun and wind conditions in urban continuums - Li, Jianong; Niu, Jianlei; Mak, Cheuk Ming (Sustainable cities and society, 2022)
•Subjects experienced different intensities of variations in wind and solar radiation while walking in urban areas;•A novel index to characterize these variations;•Transient physio-psychological responses to variations were recorded;•Influences of simultaneously varying wind and solar radiation were explored;•Intensity of simultaneous variations was quantified by skin temperature variability;•Intensifying simultaneous variations can increase the thermal acceptability. Rich, rapid, and simultaneous variations in wind and solar radiation produced by complex urban continuums are supposed to have positive effects on thermal comfort during walking. However, the identification of these influences is still challenging. In view of this, this study observed the mixed thermal perceptions and skin temperature of 70 healthy young college students when strolling in two complex urban continuums and experiencing rapid variations in sun and wind conditions. An index was proposed to categorize the varying wind and solar radiation in both numerical and geometrical respects. The results showed that, the intensities of varying wind, varying solar radiation, and air temperature simultaneously influenced the mixed thermal perceptions. Meanwhile, the intensity of simultaneously varied wind and solar radiation can be quantified by the mean skin temperature variability in a multiple linear model. An increase in the intensity of simultaneously varied wind and solar radiation led to a two-degree rise in the acceptable air temperature and a 1.2-degree increase in the mean skin temperature threshold for irritation. The study revealed the effects of simultaneously varied wind and solar radiation on pedestrian thermal comfort, motivating urban planners to take advantage of the dynamic nature created by urban morphologies to generate wind and solar radiation variations for comfort.